2002
DOI: 10.1002/1527-2648(20021014)4:10<814::aid-adem814>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Process Control in Aluminum Foam Production Using Real-Time X-ray Radioscopy

Abstract: Aluminum alloy foams were created by expanding foamable precursors containing a gas‐releasing blowing agent in a dense metallic matrix. The precursors were prepared in two different ways: either by hot‐compaction of powder mixtures or by thixocasting of billets obtained by cold compaction of powder blends. Foam evolution was visualized by means of real‐time X‐ray radioscopy with image frequencies ranging up to 18 Hz and spatial resolutions down to 10 μm. The difference in pore formation between the two process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 14 publications
1
51
0
1
Order By: Relevance
“…The transition from a stable film to an instable one is often related to its thinning [23]. This can occur in liquid metals (i) during foam expansion due to film stretching, also called growth or expansion coalescence [24]; or (ii) due to foam collapse in the course of liquid drainage from the films, reaching a critical thickness beneath which the film breaks [15,24]. For metals foamed by the action of a blowing agent, rupture of films was found with the help of microgravity experiments to be also a consequence of pressure differences between bubbles due to an inhomogeneous distribution of the gas-supplying blowing agent particles [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from a stable film to an instable one is often related to its thinning [23]. This can occur in liquid metals (i) during foam expansion due to film stretching, also called growth or expansion coalescence [24]; or (ii) due to foam collapse in the course of liquid drainage from the films, reaching a critical thickness beneath which the film breaks [15,24]. For metals foamed by the action of a blowing agent, rupture of films was found with the help of microgravity experiments to be also a consequence of pressure differences between bubbles due to an inhomogeneous distribution of the gas-supplying blowing agent particles [2].…”
Section: Resultsmentioning
confidence: 99%
“…The temporal and spatial occurrence of coalescence in metal foams was investigated in former studies with acquisition rates of up to 18 fps [15][16][17][18]. We progressed this work and analyzed the occurrence of coalescence in liquid aluminum foams with capture rates of 1250 Hz at ID-19, European Synchrotron Radiation Facility Metals 2017, 7, 298 2 of 6 (ESRF), Grenoble, France.…”
Section: Introductionmentioning
confidence: 99%
“…Gas agents can be added to aluminum alloys in die-casting or ordinary crucibles, which is called the Formgrip process [59]. Precursors used for Thixocasting are produced by pre-compacting powder mixtures to billets and heating them to the semi-solid state [60]. Liquid aluminum is sprayed and deposited on the gas agents in the Osprey casting system.…”
Section: Precursor Gas Tabletsmentioning
confidence: 99%
“…This leads gas bubbles to form from the outer surface of the metal toward the center. The development of the side cooling system guides continuous casting for metal foam production [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. …”
Section: Mold Castingmentioning
confidence: 99%
“…This technique has previously been used to reveal the temporal evolution of metal foams and to analyse the different phenomena during foaming, such as coalescence or coarsening effects. [225][226][227][228] However, there is only one study reported by Verdejo et al [229] on the use of synchrotron X-ray radioscopy on polymer nanocomposite foams, in particular silicone foams filled with CNTs and FGS. Here, initial studies are presented on the use of the X-ray radioscopy to follow the kinetics of density evolution and their relation to the kinetics of polymerisation.…”
Section: Morphological Analysismentioning
confidence: 99%